The Effect of Infrastructure Management and Work Environment on the Effectiveness of Teachers' Work in Madarasah Ibtidaiyah - Milak, Asep Saepul; Zainuddin, Ammar (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
The investigation employs a quantitative strategy utilizing a survey research methodology. The research is carried out at Private Islamic Elementary Schools in the KKMI Cluster of Pancatengah Sub-District, Tasikmalaya Regency. A Simple Random Sampling technique is applied, involving a sample size of 92 teachers. Questionnaires are used for data collection, and data analysis is conducted using SPSS version 24 for Windows. The research outcomes are outlined as follows: (1) There is a noteworthy positive impact of facility management on teachers' work effectiveness at Private Islamic Elementary Schools in the KKMI Cluster of Pancatengah Sub-District, Tasikmalaya Regency, substantiated by the computed t-value surpassing the tabulated t-value (6.626 > 1.987) with a coefficient of determination of 0.553, indicating a 55.3% influence. (2) There is a significant positive effect of the work environment on teachers' work effectiveness at Private Islamic Elementary Schools in the KKMI Cluster of Pancatengah Sub-District, Tasikmalaya Regency, validated by the calculated t-value exceeding the tabulated t-value (5.351 > 1.987) with a coefficient of determination of 0.494, signifying a 49.4% impact. (3) There is a substantial positive combined impact of facility and infrastructure management and the work environment on teachers' work effectiveness at Private Islamic Elementary Schools in the KKMI Cluster of Pancatengah Sub-District, Tasikmalaya Regency, confirmed by the computed F-value surpassing the tabulated F-value (86.960 > 3.10) with a coefficient of determination of 0.661, indicating a 66.1% effect. In summary, both facility and infrastructure management and the work environment positively and significantly influence teachers' work effectiveness at Private Islamic Elementary Schools in the KKMI Cluster of Pancatengah Sub-District, Tasikmalaya Regency, both individually and collectively. This study suggests that all stakeholders should actively manage and maintain facilities and infrastructure while preserving the school's work environment to enhance teacher effectiveness consistently.